2014
DOI: 10.1111/jbi.12330
|View full text |Cite
|
Sign up to set email alerts
|

Timing the diversification of the Amazonian biota: butterfly divergences are consistent with Pleistocene refugia

Abstract: Rejection of the Pleistocene refugium hypothesis (PRH) as an explanation for the high biodiversity of Neotropical forest is based in part on the assertion that biotic elements of these forests evolved during the Neogene. That argument is justified, in turn, by the ages of crown groups (the age of the most recent common ancestor of extant species of a clade). We consider the use of crown ages as a metric to reject the PRH to be an unfair test, because the circumscription of crown groups of interest is arbitrary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
66
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 64 publications
2
66
0
Order By: Relevance
“…Garzón‐Orduña et al . (, p. 1631) found that ‘…72% of speciation events leading to the formation of butterfly sister species occurred within the last 2.6 Myr [the Pleistocene]…’ and concluded that ‘…the PRH [Pleistocene refuge hypothesis] cannot be completely discarded as a driver of Neotropical diversification’. In their analysis, Garzón‐Orduña et al .…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Garzón‐Orduña et al . (, p. 1631) found that ‘…72% of speciation events leading to the formation of butterfly sister species occurred within the last 2.6 Myr [the Pleistocene]…’ and concluded that ‘…the PRH [Pleistocene refuge hypothesis] cannot be completely discarded as a driver of Neotropical diversification’. In their analysis, Garzón‐Orduña et al .…”
mentioning
confidence: 83%
“…Garzón‐Orduña et al . () used DNA molecular phylogenies to estimate the age of speciation of Neotropical butterflies in their contribution to the debate about the timing and causes of Neotropical diversification. These authors addressed the problem using species dating (estimating the age of divergence of sister species) instead of crown dating (estimating the age of the initial diversification of supra‐specific clades), as it has been suggested that, in general, crown dating tends to overestimate the chronological origin of diversity (Rull, ,b).…”
mentioning
confidence: 99%
“…The paucity of data for South American species, particularly for those adapted to open and/or dry habitat types, has greatly hindered the understanding about diversification mechanisms in the continent (Hughes et al, 2013;Turchetto-Zolet et al, 2013). Despite the controversy about Haffer's (1969) forest refuge hypothesis (for example, Hoorn et al, 2010;Rull 2011), many species associated with mesic vegetation display similar patterns (Turchetto-Zolet et al, 2013;Garzón-Orduña et al, 2014) that are consistent with the tropical refugial hypothesis. This is not true for species occurring in xeric and open environments as the rocky savanna habitats in Eastern South America, which show more idiosyncratic patterns (Turchetto-Zolet et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The investigation into the effect of historical climatic changes on the distribution and population dynamics of species has been a major focus of phylogeography (Hewitt, 1996;Avise et al, 1998;Taberlet et al, 1998;Soltis et al, 2006;Garzón-Orduña et al, 2014). Most of these studies focused in the Northern Hemisphere (Beheregaray, 2008), and tried to identify putative species refugia by locating regions of the species' range that contain high levels of genetic diversity and were also ice-free during glaciation (Keppel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…12) or the Pebas system, a large network of shallow lakes and wetlands, which occupied the upper Amazon region, may have constrained dispersal and promoted local diversification until its drainage around 10-7 million years ago1314. It is also suggested that climatic instability during the Pleistocene drove the diversification of extant Neotropical species, but the importance of this mechanism remains controversial9151617181920.…”
mentioning
confidence: 99%